Oil in Ecuador, 2000-2015: curse, blessing or just a resource? - Caria, Sara (Iberoamerican Journal of Development Studies, 2017)
Oil has been Ecuador’s most important export product since the 70’s; the current low prices of commodities have placed the need of a productive diversification in the center of the debate about development strategies. In this paper, it is aimed at establishing whether the dependence on oil’s exports has been an obstacle for the diversification of Ecuadorian economy during the recent commodities boom (2003-2014), as the «product trap» thesis suggests. For this purpose, a survey on the literature about the so called «resources’ curse» will be made in order to identify the main rationales that support this thesis and the policy recommendations that literature on this topic suggests to oil-rich countries. Then, the Ecuadorian case will be analyzed to search evidence that confirm the existence of an «oil curse» in Ecuador. The results show that oil dependence and low diversification are empirically associated, but no clear causal relation can be established between them.